Towards a zero hunger world through nutriceral pearl millet - Satyavathi, C. Tara; Rawal, Pokhar; Khandelwal, Vikas (Indian Farming, 2018)
Pearl millet is primarily grown for food and dry fodder. Its grains are highly nutritious with high levels of metabolizable energy and protein. It has high iron (Fe) and zinc (Zn), and more balanced amino acid profile compared to rice, wheat, maize or sorghum. Grains are mainly used for human consumption as leavened and unleavened flat breads and porridges. Dry stover of pearl millet is a major component of livestock ration during the dry period of year. Pearl millet is also an excellent forage crop. Its green fodder is rich in protein, calcium (Ca), phosphorous (P) and other minerals with oxalic acid within limits.